Synergistic Integration of Probiotics and Nanotechnology: Advanced Therapeutic Strategies for Geriatric Drug Delivery, Hyperthermia, and Wound Management (Development Engineering Conferences Center Articles Database, 2025)
The convergence of probiotic science and nanotechnology offers a paradigm-shifting strategy for managing age-related health conditions, with specialized applications in targeted drug delivery, hyperthermia treatment, and chronic wound care. This comprehensive review examines the collaborative potential of probiotic-derived gold nanoparticles (AuNPs) and nano-encapsulation platforms in augmenting therapeutic outcomes for elderly patients. Probiotic-synthesized AuNPs exhibit substantial anti-inflammatory properties through suppression of NF-κB/MAPK signaling cascades, markedly decreasing pro-inflammatory cytokine production in both cellular and animal models. Nano-encapsulation methodologies employing chitosan, PLGA, and electrospun nanofibers safeguard probiotic viability under adverse gastrointestinal conditions while facilitating regulated release and site-specific delivery. These sophisticated platforms demonstrate considerable potential in photothermal treatment, tissue regeneration, and gut microbiome regulation, providing enhanced bioavailability and diminished toxicity relative to conventional approaches. Nevertheless, challenges related to mass production capabilities, regulatory endorsements, and extended stability require resolution prior to clinical implementation. The merger of probiotic technology with advanced nanotechnology introduces an innovative framework for creating personalized, biologically responsive treatments targeting chronic inflammation, multidrug-resistant infections, and metabolic disorders associated with aging.